Sobrecarga w sofrimento psíquico em familiares de portadores de transtorno de pânico com agorafobia - Borgo, Evandro Luis Pampani [UNESP] (2014)
Introduction: There are many reasons for family members of patients with mental disorders to suffer and feel burdened. Psychiatric patients may present inappropriate behaviors and functional impairments, becoming dependent on others. This situation can have a negative impact on the lives of family members, especially the caregivers. There are several studies to measure this impact on caregivers, but they are mainly about major mental disorders, such as schizophrenia and dementia. High levels of family burden were also observed among Obsessive-Compulsive Disorder (OCD) caregivers, but there are no studies on family burden and distress among Panic-Agoraphobic Disorder (PAD) caregivers. The main PAD features are: intense, unexpected and recurrent panic attacks in association with anticipatory anxiety and avoidance of places and/or situations due to fear of having another panic attack. So, in general, the patients become dependent upon family members for assistance in daily life activities. Objective: To estimate the prevalence and severity of the burden and psychological suffering (common mental disorder - CMD) in family members of patients with PAD. Method: It is a cross-sectional study, with a clinical sample of adults with PAD diagnosis (DSM-IV criteria), receiving treatment from a private clinic in Bauru and also at an outpatient service (Ambulatório de Transtornos Ansiosos e Obsessivo-Compulsivos- ATAOC) of the Botucatu Medical School (UNESP), State of São Paulo -Brazil, between January 2011 and October 2013. The assessment instruments used to evaluate the caregivers were: a questionnaire with sociodemographic data, the Carer Burden Interview (CBI), the Brazilian version of the Family Burden Interview Scale (FIBS-BR) and the Self-Reporting Questionnaire (SRQ). The instruments to assess the patients were: a questionnaire with sociodemographic and clinical data, the Panic and Agoraphobia Scale (PAS) to evaluate the severity of ...